Nanoencapsulation of sulforaphane in broccoli membrane vesicles and their in vitro antiproliferative activity - Lucía Yepes-Molina; Micaela Carvajal (Taylor & Francis Group, 2021)
Context The development of nanocarriers of plant origin, such as plant cell membranes, has recently been investigated. Also, plant bioactive compounds as sulforaphane (SFN) from broccoli have recognized antioxidant or anticancer properties. Objective To investigate the capacity of membrane vesicles from broccoli (BM-vesicles) to encapsulate SFN and their application in the cancer cell line. Materials and methods Physicochemical analysis was carried out to characterize BM-vesicles through different approaches: dynamic light scattering, transmission electron microscopy, stopped-flow analysis, and proteomic analysis. They were applied at different concentrations (BM-vesicles at 0.04-0.00315% of protein and SFN at 5, 25, and 100 µM) in SK-MEL-28 cells during 24 h for studying cytotoxicity and gene expression. Results The entrapment efficiency was 41%. The anticancer activity tested in cells showed a decrease in proliferation when SFN in BM-vesicles was utilized. Expression patterns when SFN was applied in an encapsulated form showed a reduction of cancer markers and an increase of AQP3. Also, the metabolism of SFN occurred inside of cells, and higher SFN penetrated when it was encapsulated. Discussion The results showed that encapsulated SFN was better absorbed by melanoma cells providing metabolism products and a reduction of cancer molecular markers. Also aquaporin, AQP3 was pointed to as an important marker since it appeared to play a key role in homeostasis due to the importance of water transport in biological processes. Conclusion These results indicate that SFN and SFN encapsulated in BM-vesicles have a high activity for the inhibition of melanocyte development. Therefore, BM-vesicles could serve as nanocarriers for drugs.